Penerapan Hierarki Norma dalam Putusan Mahkamah Konstitusi atas UU Kesehatan Tahun 2023: Analisis Teori Stufenbau - Mohamad Ihsan Ramdani (Pusat Riset dan Inovasi Nasional, 2026)
This article analyzes the application of the hierarchy of norms in the decisions of the Constitutional Court concerning Law Number 17 of 2023 on Health using the perspective of Hans Kelsen’s Stufenbau theory. The enactment of the Health Law has generated significant legal debate and several constitutional review petitions submitted to the Constitutional Court, raising questions about the consistency between statutory norms and constitutional principles. This study aims to examine how the Constitutional Court applies the principle of hierarchical norms in reviewing the constitutionality of the Health Law and to assess the relevance of Stufenbau theory in explaining the interpretation of legal norms in constitutional adjudication. This research employs a normative juridical method using statute, conceptual, and case approaches. Primary legal materials consist of the 1945 Constitution, Law Number 17 of 2023 on Health, and relevant Constitutional Court decisions, supported by secondary legal materials from academic literature and legal studies. The findings show that the Constitutional Court consistently positions the 1945 Constitution as the highest norm within the Indonesian legal system and uses the hierarchy of norms as the basis for evaluating the validity of statutory provisions. The Court maintains the legal force of the Health Law when no normative conflict with the Constitution is identified, while in certain cases it provides constitutional interpretation to ensure the compatibility of statutory norms with constitutional principles. This study demonstrates that Stufenbau theory remains relevant as an analytical framework for understanding the hierarchical structure of legal norms and the operation of constitutional review within the Indonesian legal system.